Systematic analyses with genomic and metabolomic insights reveal a new species, Ophiocordyceps indica sp. nov. from treeline area of Indian Western Himalayan region - Sharma, Aakriti; Kaur, Ekjot; Joshi, Robin; Kumari, Pooja; Khatri, Abhishek; Swarnkar, Mohit Kumar; Kumar, Dinesh; Acharya, Vishal; Nadda, Gireesh (Frontiers in Microbiology, 2023)
Ophiocordyceps is a species-rich genus in the order Hypocreales (Sordariomycetes, Ascomycota) depicting a fascinating relationship between microbes and insects. In the present study, Aa new species, Ophiocordyceps indica sp. nov. is discovered infecting lepidopteran larvae collected from tree line locations (2202-2653 m AMSL) of the Kullu District, Himachal Pradesh, Indian Western Himalayan region, using combinations of morphological and molecular phylogenetic analyses. A phylogeny for Ophiocordyceps based on a combined multigene (nrSSU, nrLSU, tef-1α, and rpb1) dataset is provided and its taxonomic status within Ophiocordycipitaceae is briefly discussed. Its genome size (~59 Mb) revealed 94% genetic similarity with O. sinensis, however, it differs from other extant Ophiocordyceps species based on morphological characteristics, molecular phylogenetic relationships, and genetic distance.O. indica is identified as the second homothallic species in the family Ophiocordycipitaceae, after O. sinensis. The presence of targeted marker components viz. nucleosides (2303.25 µg/g), amino acids (6.15%), mannitol (10.13%), and biological activity data suggest it to be a new potential source of nutraceutical importance. Generated Ddata generated around this economically important species will expand our understanding regarding the diversity of Ophiocordyceps-like taxa from new locations, thus providing new research avenues.